A novel enrichment approach for anaerobic digestion of lignocellulosic biomass: Process performance enhancement through an inoculum habitat selection. (October 2020) - Ferraro, Alberto; Massini, Giulia; Mazzurco Miritana, Valentina; Rosa, Silvia; Signorini, Antonella; Fabbricino, Massimiliano
Graphical abstract: Highlights: Microbial enrichment procedure was proposed for anaerobic digestion of wheat straw. Sequential re-inoculum with rumen-mimicking supports was tested at different timing. Porous supports and re-inoculum time significantly affected the biogas composition. Microbial functional diversity was promoted by the porous supports involvement. Lower and higher re-inoculum times enhanced the H2 and CH4 productions respectively. Abstract: Inocula enrichment was performed using an innovative habitat-based selection approach to improve wheat straw (WS) anaerobic digestion (AD) efficiency. The procedure was carried out by sequentially re-inoculating the primary microbial community seven times in subsequent anaerobic reactors containing untreated WS. Re-inocula were performed at different re-inoculum times (24, 48, and 96 h) by moving a porous support mimicking a rumen structure from one batch to the next (S-tests) or re-inoculating only the culture medium (C-tests). Highest H2 production yields were observed after four and five re-inocula (0.08 ± 0.02 NmL h −1  gVS −1 and 0.09 ± 0.02 NmL h −1  gVS −1 ) for S-24 and S-48, respectively. For S-96, higher CH4 yields were observed after the start-up test and sixth re-inoculum (0.05 ± 0.003 NmL h −1  gVS −1 and 0.04 ± 0.005 NmL h −1  gVS −1, respectively). Accordingly, S-96 showed the highest active Archaea component (7%). C-test microbial communities were dominated by fermenting, hydrogen-producing bacteria and showed lower microbial community diversity than S-tests.